Moss diversity: a molecular phylogenetic analysis of genera - Cox, C. J. (2014)
In this study we present phylogenetic and molecular phylogenetic diversity analyses of moss taxa from a total of 655 genera of mosses. Three loci were sampled: chloroplast ribosomal small protein 4, the intronic region of the mitochondrial NADH dehydogenase subunit 5, and partial sequences of the nuclear 26S ribosomal RNA. Maximum likelihood and Bayesian phylogenetic analyses were performed on individual loci and on multilocus data sets. A measure of phylogenetic diversity was calculated and constrasted among major lineages of mosses. We reveal many instances of incongruence among genomic partitions, but, overall, our analyses describe relationships largely congruent with previous studies of the major groups of mosses. Moreover, our greater sampling highlights the possible non-monophyly of many taxonomic families, particularly in the haplolepideous and pleurocarpous mosses. Comparisons of taxic and phylogenetic diversity among genera indicate that the Dicranidae (haplolepideous taxa) include about 15% of moss genera, but nearly 30% of the phylogenetic diversity. By contrast, the Hypnanae (hypnalian pleurocarps) contain about 45% of moss genera, but a lower percentage of phylogenetic diversity. Agreement between numbers of genera and phylogenetic diversity within other moss clades are remarkably consistent.